Effect of Tungsten Oxide Nanostructures on Sensitivity and Selectivity of Pollution Gases - Fenghui An; Andrew F. Zhou; Peter X. Feng (Sensors, 2020)
We report on the different surface structures of tungsten oxides which have been synthesized using a simple post-annealing-free hot-filament CVD technique, including 0D nanoparticles (NPs), 1D nanorods (NRs), and 2D nanosheet assemblies of 3D hierarchical nanoflowers (NFs). The surface morphologies, crystalline structures, and material compositions have been characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and Raman spectroscopy, respectively. The sensor performances based on the synthesized samples of various surface morphologies have been investigated, as well as the influences of operating temperature and applied bias. The sensing property depends closely on the surface morphology, and the 3D hierarchical nanoflowers-based gas sensor offers the best sensitivity and fastest response time to NH3 and CH3 gases when operated at room temperature.